2012
DOI: 10.4236/fns.2012.32031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Physicochemical and Microbial Quality of Ultrasound-Treated Apple-Carrot Juice Blends

Abstract: Three different apple-carrot juice blends (60:40, 75:25 and 90:10, v/v) were prepared and treated with ultrasound with comparison to the conventional thermal pasteurization. Total aerobic viable count (TAC) were significantly lower in juice blends with lower pH (apple-carrot ratio of 90:10, v/v) than the blends with higher pH after one month storage at 4˚C. TAC were similar in ultrasound-treated and thermal pasteurized juice blends. Changes of turbidity of juice during storage followed the same pattern of TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
14
18
2
Order By: Relevance
“…In general, the maximum effect of sonication was observed after 2 weeks of refrigeration. A similar result was reported for carrot/apple juices, where the decrease in TVC was observed 14 days after sonication; however, it also seemed to be related to pH and juice composition (Gao and Vasantha Rupasinghe (2012). The pH progressively decreased during the storage time (from 3.6 to 3.2) but the differences were only significant after 28 days ( Figure S1).…”
Section: Storage Testsupporting
confidence: 84%
See 2 more Smart Citations
“…In general, the maximum effect of sonication was observed after 2 weeks of refrigeration. A similar result was reported for carrot/apple juices, where the decrease in TVC was observed 14 days after sonication; however, it also seemed to be related to pH and juice composition (Gao and Vasantha Rupasinghe (2012). The pH progressively decreased during the storage time (from 3.6 to 3.2) but the differences were only significant after 28 days ( Figure S1).…”
Section: Storage Testsupporting
confidence: 84%
“…These data suggested that for a sonicated juice under refrigeration, the shelf life of the aroma could be taken to be 14 days. The link between organoleptic deterioration and microbial activity was also suggested for sonicated orange juices (with calcium citrate), where sonication prolonged the shelf life of 4 days (Gao & Vasantha Rupasinghe, 2012). The sonication treatment applied was the highest tested before sensory change (e.g.…”
Section: Linear Discriminant Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…This might be due to increase in titrable acidity, as acidity and pH are inversely proportional to each other. Majumdar [24,25] also reported similar results for a juice blend of bottle guard and basil leaves juice.…”
Section: Ascorbic Acidsupporting
confidence: 63%
“…Recently, an increasing interest in the consumption of blended vegetable and fruit juices has been observed and it seems that mixed carrot-fruit juice (mainly with apples, bananas, oranges) are preferred and recommended to people of all ages (Gao and Rupasinghe 2012;Jan and Dorcus Masih 2012;Leahu et al 2013;Winiarska-Mieczan and Nowak 2008). The blending of juices may improve their aroma, taste, and nutritional value as well as lead to obtain new beverages (Bhardwaj and Pandey 2011;Jan and Dorcus Masih 2012;Suna et al 2013).…”
Section: Introductionmentioning
confidence: 96%